Accelerator programming using directives : 6th International Workshop, WACCPD 2019, Denver, CO, USA, November 18, 2019, Revised selected papers /: 6th International Workshop, WACCPD 2019, Denver, CO, USA, November 18, 2019, Revised selected papers. (2020) - Unknown
No abstract available